Desempenho de arrecadação e inscrição em restos a pagar: um estudo nos municípios brasileiros - Silva, Vanessa Ferreira da (2023)
Based on the theory of public choice and on the literature on public budget, this study aims to analyze the influence of the collection performance on the inscription of expenses in unpaid balances in Brazilian municipalities. To this end, the theoretical assumption is presented that agents invested in their government functions make decisions not only based on the public interest, but also aiming to maximize their own interests. Thus, we sought to investigate the use, by public managers, of budget estimates of revenue in a discretionary way, with their overestimation, to have more freedom to manage and expand public expenditures in strategic periods through the remains to be paid. To carry out the research, Brazilian municipalities (5,568 entities) were selected as universe and sample, in the period from 2015 to 2021. Data collection and tabulation was carried out with the aid of electronic spreadsheets, with subsequent structuring in an unbalanced panel and, for analysis from the data, quantitative methods were used, which consisted of descriptive statistics and the regression technique with panel data, fixed effects model. For statistical and econometric analysis, the Indicator of Enrollment in Remains Payable (IRP) was established as a dependent variable, measured by the quotient between the inscribed remains to be paid (processed and unprocessed) and the committed budgetary expenditure and, as an independent variable, the Indicator Collection Performance (IDA), measured by the quotient between expected and collected budget revenue. The results obtained indicated that the collection performance positively and statistically significantly influences the level of inscription of expenses in remains payable by the municipalities (H1). In addition, it was demonstrated that both registration in remaining payables and collection performance are influenced by the electoral calendar, with an increase in the levels of overestimation of revenue and registration in remaining payables in the pre-election year and a reduction, opportunely, in the election year. In this way, the proposed research hypothesis (H1) can be confirmed, so that the findings of this study corroborate the theoretical assumptions of Public Choice, that the public budget is sensitive to the discretionary choices of managers, adopted in a discretionary way to serve their own interests.